Message - Zhu, Dr. George (Universal Journal of Pharmaceutical Research, 2019)
The UJPR has grown up for two years. From aim and scope of UJPR, it has been covering a broad of multidisciplinary areas in pharmaceutical science including basic fields, molecular images, clinical trials and other medical practice, to increase the impact factor of journal. A considerable fact provide strong validation that authors might prepare high quality of their intensive original researches, the subject of pharmaceutical molecular mechanism of drugs, and the systemic exploration of medicinal herbs among folk medicines. In vitro and in vivo transgene experiments are continued ongoing. In clinical classical trials, the earliest palliative treatment of metastatic breast cancer by oophorectomy was initially reported by George Thomas Beatson in 1896, the father of anti-hormonal treatment of breast cancer. This implicate anti-hormonal tumorigenesis,which linked hormonally-driven cancers. Tumor cells share oncogenic receptor (Robinson R). It is previously reported that among these oncogenic receptor derivatives, oncogenic activating prolactin (PRL)/PRL receptor signaling linked to hyperprolactinemia and breast tumorigenesis; aberrant expression of lysophosphatidic acid receptor mediated the tumorigenicity of hepatocellular carcinoma (HCC) (Mazzocca A); and an additional member of vitamin K dependent Gas6 and protein S/Axl oncogenic receptor signalling (Burstyn-Cohen T;O’Bryan JP etal,1991; Hafizi S et al., 2006). Prolactin, phospholipid, growth hormone, vitamin A and protein S are natural substances in human body and important medicine. In recent advances, genetic deficiency of EpCAM was identified as the gene for congenital tufting enteropathy (Sivagnanam M; Kozan PA). An inherited defects in reduced cell membrane EGFR (the EGFR signaling ablation due to a loss-of-function mutation p.Gly428Asp) has been recorded in an infant with epithelial inflammation (Campbell P). I also consulted a tumoral girl with her abdominal much thinner and transparent epidermis, and with pustules. At present, pharmaceutical effects of monoclonal antibodies targeting directed oncogenic receptor immunotherapy (for examples oncogenic receptor EpCAM, oncogenic receptor EGFRv III, HER2 oncogenic receptor, oncogenic receptor derivative pml/RARa or also oncogenic pml/ RARa) moves initially patients trials to front center. Downregulating oncogenic receptors may be useful paradigm in currently the third line setting of clinical target therapy and in rendering our highlight on the understanding of cancer biology. It is at ’ hot spot ’ topics today. After browsing those publications in UJPR, each of the contributors was represent to analyze the most notable advances in his or her area and to also provide a critical interpretative review from his or her own unique perspective. Obviously, it would be better to leave that to the judgment of each contributor. Actually, UJPR is now recognized as an international and indexed journal in more than 40 locations and I think that our journal will achieve an impact factor and will be member of Scopus, ISI and NLM category number (Abstracts indexed in PubMed, NCBI/PMID) in nearest future. This is all our wishes.